2020
DOI: 10.2478/afpuc-2020-0003
|View full text |Cite
|
Sign up to set email alerts
|

Concentration-dependent effect of silymarin on concanavalin A-stimulated mouse spleen cells in vitro

Abstract: Aims: Silymarin (SIL), a mixture of phenolic compounds, has a pleiotropic mode of action on various cell types, including immune cells. In this study, we investigated the concentration-dependent effect of SIL on proliferation of concanavalin A (CoA)-stimulated mouse spleen T lymphocytes, their viability, and secretion of IFN-g and IL-4 cytokines ex vivo in relation to gene expressions of transcription factors nuclear factor kappa B and Foxp3. In addition, metabolic activity of T cells was determined as changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…An essential function of flavonoids is the reduction of inflammatory markers, cytokine expression, modulation of transcription factors, and the effect on transduction signals. Silymarin inhibition of the NF‐κB pathway (Hrčková, Mačák Kubašková, Mudroňová, & Bardelčíková, 2020 ) has a potential therapeutic role in alleviating the severe form of COVID‐19. Ginkgetin, a biflavonoid from Ginkgo biloba, effectively decreased the expression of inflammation‐related protein prostaglandin E2 (PGE2), tumor necrosis factor‐alpha (TNF‐α), interleukin‐1β (IL‐1β), interleukin‐6 (IL‐6), and interleukin‐8 (IL‐8) (Q. Li et al, 2019 ).…”
Section: Flavonoidsmentioning
confidence: 99%
“…An essential function of flavonoids is the reduction of inflammatory markers, cytokine expression, modulation of transcription factors, and the effect on transduction signals. Silymarin inhibition of the NF‐κB pathway (Hrčková, Mačák Kubašková, Mudroňová, & Bardelčíková, 2020 ) has a potential therapeutic role in alleviating the severe form of COVID‐19. Ginkgetin, a biflavonoid from Ginkgo biloba, effectively decreased the expression of inflammation‐related protein prostaglandin E2 (PGE2), tumor necrosis factor‐alpha (TNF‐α), interleukin‐1β (IL‐1β), interleukin‐6 (IL‐6), and interleukin‐8 (IL‐8) (Q. Li et al, 2019 ).…”
Section: Flavonoidsmentioning
confidence: 99%
“…It has been demonstrated that there are strong direct scavengers of some free radicals ( Dehmlow et al ., 1996 ). It is well documented, that silymarin/silybin can decrease oxidative stress and has a protective effect on mitochondrial structure ( Rolo et al ., 2003 ) and immune cells function ( Hrčková et al ., 2020a ). There are also well documented antioxidant protective properties of silymarin/silybin in the prevention of toxic effects of various chemicals, such as arsenic, carbone tetrachloride, mycotoxins, thioacetamide, cisplatin, manganese, etc.…”
Section: The Effects Of Curcumin On Flatwormsmentioning
confidence: 99%